THEORETICAL FOUNDATIONS OF ADVENTURE TOURISM AND ITS IMPORTANCE IN TOURISM EDUCATION (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Despite its importance, adventure tourism has received less scholarly attention. The most relevant research comes from outdoor recreation. The research focuses on psychological aspects such as thrills, conflicts, and norms, safety concerns such as injuries and insurance, environmental, social, and economic implications, and involvement and management. Little research has been conducted on the structure of adventure tourism products and their business features. Future study topics include operational audits, commercial statistics, client profiles, site geography, equipment manufacturing, safety and insurance, recreation ecology, adventure destination marketing, and the relationship between amenity migration and lifestyle.Adventure tourism is a significant but understudied field in tourist education. As a result, in order to determine future goals, the study go over the major subjects addressed in adventure tourism research thus far. This review does not seek to summarize the conclusions of each individual published study, but rather to identify the significant trends in the research literature as a whole. To make this as simple as feasible, clusters of similar references are presented in tabular format.